Anthropogenic Disturbances on the Regeneration of Tree Species in the Mixed Broadleaved Forest of the Himalayan Region, Nepal - Giri, Anjana; Katzensteiner, Klaus (Journal of Natural History Museum, 2015)
The aim of this study was to assess the anthropogenic impacts on the vegetation structure and regeneration of dominant tree species in the community managed mixed broadleaved forests of the Sargamatha (Everest) National Park buffer zone area. The forest plots were categorized into disturbed and semi-disturbed considering the scale of anthropogenic disturbances such as percentage of biomass extraction, lopping, tramping coverage and grazing intensity. For each forest type, three radii (10 m, 5 m and 2.5 m) plots were laid for sampling trees, sapling and seedling layers, respectively. In both the forest sites, Quercus semecarpifolia and Rhododendron arboreum were the main dominant tree species. The distribution of Q. semecarpifolia and R. arboreum along with diameter classes showed high stem density mainly concentrated in 2-15 cm diameter class. In both sites, the density of R. arboreum showed increment from sapling to seedling stage, while no seedling of Q. semecarpifolia was recorded in the disturbed site. The absence of Q. semecarpifolia seedlings in the disturbed forest sites could be associated with the practice of biomass removal and forest management activities. The study attributed that Rhododendron species in the study sites were not frequently cut, browsed, or lopped due to their religious belief and its ornamental value. Thus R. arboreum is expected to be slowly expanded if biotic pressure is maintained less. This may cause change in the vegetation structure and scarcity of resources for livelihood. On the whole, managing the forest in an equitable and sustainable way could satisfy basic needs and improve the livelihood of rural people in the study area. J. Nat. Hist. Mus. Vol. 27, 2013: 35-44